The national traditions and development of Multiculturalizm in Azerbayijan - Бaлaевa, Г. Е. (Journal of Oriental Studies, 2018)
This article deals with Azerbaijan National traditions, multicultural value and the projektion of multiculturalism in education. In this saving from other peoples, traditions being as a multicultural people, organizing summer schools being as a multicultural year of 2017 in Azerbaijan had been reflected.